Sulfonic acid/sulfur trioxide (SO3H/SO3) functionalized two-dimensional MoS2 nanosheets for high-performance photocatalysis of organic pollutants. (29th June 2022) - Singh, Vivek Kumar; Jain, Prachi; Panda, Subrata; Kuila, Biplab Kumar; Pitchaimuthu, Sudhagar; Das, Santanu
Abstract : We report the enhanced photocatalytic activity of sulfonic acid/sulfur trioxide (SO3 H/SO3 ) functionalized two-dimensional (2D)-MoS2 (SO3 H/SO3 -MoS2 ) nanosheets synthesized using a one-pot hydrothermal method. Abstract : We report the enhanced photocatalytic activity of sulfonic acid/sulfur trioxide (SO3 H/SO3 ) functionalized two-dimensional (2D)-MoS2 (SO3 H/SO3 -MoS2 ) nanosheets synthesized using a one-pot hydrothermal method. The functionalization causes the expansion of MoS2 interlayers and widening of the bandgap while keeping the basal plane intact, thereby improving the catalytically active surface sites and low charge recombination rates. The photocatalytic activity of SO3 H/SO3 -MoS2 was evaluated by calculating the rate constant of ∼0.06728 min −1 while the dye degradation time was obtained as ∼50 min (10 ppm), which was faster compared to those of the bulk MoS2 and pristine 2D-MoS2 nanosheets under identical conditions. The enhancement in the photocatalytic rate-kinetics of SO3 H/SO3 -MoS2 was accomplished owing to the widening of the bandgap, the expanded 2D-MoS2 interlayers, the improved surface adsorption/desorption, and the enhanced redox properties as a result of the faster charge-transfer.